Synthesis of Cu/Co-hybrid MOF as a multifunctional porous compound in catalytic applications, synthesis of new nanofibers, and antimicrobial and cytotoxicity agents - Asiri, Mohammed; Jawad BahrAluloom, Yamamah; Abdullateef Alzubaidi, Mazin; Mourad Mohammed, Ibrahim; Suliman, Muath; Ramzy Muhammad, Eman; Abed, Ahmed S.; Abodi Ali, Fattma; Hadrawi, Salema K.; Alsalamy, Ali H.; Alwave, Marim (Frontiers in Materials, 2023)
Several biological properties of metal–organic frameworks (MOFs) and fiber compounds have been reported, and combinations of these structures can have unique properties. In this study, copper-containing and cobalt-containing MOF nanostructures were synthesized by the ultrasonic technique. Then, novel Cu/Co-hybrid MOF nanostructures were synthesized using the ultrasonic method. Synthesized Cu/Co-hybrid MOF nanostructures were used as a new and efficient recyclable catalyst in the synthesis of pyrano[2,3-c]pyrazole derivatives using the four-component reaction of phenylhydrazine, ethyl acetoacetate, malononitrile, and aldehyde. In the following, novel Cu/Co-hybrid MOF/PVA (poly vinyl alcohol) fiber nanostructures were synthesized by electrospinning and using Cu/Co-hybrid MOF nanostructures and PVA. The structures of the Cu/Co-hybrid MOF nanostructures and the Cu/Co-hybrid MOF/PVA fiber nanostructures were identified and confirmed using BET, TGA, FTIR, SEM, and XRD. In biological studies, the antibacterial, antifungal, and cytotoxicity activities of Cu/Co-hybrid MOF and Cu/Co-hybrid MOF/PVA fiber nanostructures were evaluated. In investigating the catalytic activity of Cu/Co-hybrid MOF, pyrano[2,3-c]pyrazole derivatives were synthesized with higher efficiency and less time than previously reported methods. High antibacterial (against gram-negative and gram-positive strains) and antifungal properties of synthesized Cu/Co-hybrid MOF nanostructures and Cu/Co-hybrid MOF/PVA fiber nanostructures were observed (MIC between 16 and 256 μg/mL), which were higher than some commercial drugs. In the investigation of cytotoxicity activity, the effectiveness on breast cancer cells was studied. The maximum cell proliferation and viability for Cu/Co-hybrid MOF and Cu/Co-hybrid MOF/PVA fiber nanostructures were 38% and 38% higher than the control in a concentration of 200 μg/mL after 48 h. The high catalytic and biological properties of the synthesized nanoparticles can be attributed to the presence of nano-sized bioactive metals and their high specific surface area. The significant physical-chemical properties obtained for synthesized nanoparticles in this study can be related to the desirable synthesis methods, the development of materials with high purity, and the incorporation of hybrid compounds into the nanostructures.